Edukasi dan Deteksi Dini Sindrom Metabolik pada Masyarakat Desa Porame, Kecamatan Kinovaro, Provinsi Sulawesi Tengah - Viere Allanled Siauta; Muh. Fardiansyah; Meliana Herniwati Posuka (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Metabolic syndrome is a complex metabolic disorder that includes the metabolism of carbohydrates, lipids and proteins which is known to be the main cause of diabetes mellitus, hypertension and coronary heart disease. Porame Village, Kinovaro District is one of the villages with high cases of metabolic syndrome. The purpose of this activity is to provide education to the public about metabolic syndrome with the lecture method followed by examinations to detect the presence of metabolic syndrome, namely measuring blood pressure, checking fasting blood glucose levels and checking triglyceride levels using the Point of Care Testing method. The results of this activity were that 29 out of 50 participants (58%) had metabolic syndrome with an average blood pressure of 135/100 mmHg, an average fasting blood glucose level of 152 mg/dL, and an average triglyceride level of 198 mg/dL. It is hoped that there will be serious attention by local health workers and related parties to continue to carry out education and preventive efforts to prevent complications of metabolic syndrome.